+0  
 
0
733
1
avatar

Wie löst man diese Gleichung nach x auf?

0,5x^3-1,5*(a+1)*x^2+6at-120 = 0,5x^3-1,5*(b+1)*x^2+6bt-120

Ich komme am Ende immer nur dazu, t rauszukürzen!

 27.01.2016
 #1
avatar+12220 
0

Hallo, guten morgen Gast!

 

0,5x^3-1,5*(a+1)*x^2+6at-120 = 0,5x^3-1,5*(b+1)*x^2+6bt-120

 

-1,5*(a+1)*x^2+6at = -1,5*(b+1)*x^2+6bt                  [ / 1,5

-(a+1)*x^2+4at = -(b+1)*x^2+4bt 

(b + 1 - a - 1) * x² = 4t * (b - a)

(b - a) * x² = (b - a) * 4t

x² = 4t    

 

x = 2 √ (t)

 

Gruß asinus :- )

laugh!

 28.01.2016

57 Benutzer online

avatar
avatar
avatar